2015
DOI: 10.1159/000381244
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Provision of Safe Drinking Water on School Absence Rates in Cambodia: A Quasi-Experimental Study

Abstract: Background: Education is one of the most important drivers for helping people in developing countries lift themselves out of poverty. However, even when schooling is available absenteeism rates can be high. Recently, focus is being given on whether or not WASH interventions can help reduce absenteeism in developing countries. However, none has focused exclusively on the role of drinking water provision. We report a study on the association between absenteeism and provision of treated water in containers mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…These studies often focus on water and sanitation facilities at the school level (Jasper et al, 2012) and not at the community level. The provision of treated drinking water in schools helped reduce absenteeism in Cambodia (Hunter et al, 2014) and in the Nyanza Province of Kenya (Freeman et al, 2012). Similar results have been found for Indonesia (Duflo, 2001) and a number of other low-income countries (Jasper et al, 2012).…”
supporting
confidence: 61%
“…These studies often focus on water and sanitation facilities at the school level (Jasper et al, 2012) and not at the community level. The provision of treated drinking water in schools helped reduce absenteeism in Cambodia (Hunter et al, 2014) and in the Nyanza Province of Kenya (Freeman et al, 2012). Similar results have been found for Indonesia (Duflo, 2001) and a number of other low-income countries (Jasper et al, 2012).…”
supporting
confidence: 61%
“…In Cambodia, a quasi-experimental study found reductions in absence from provision of safe drinking water, though only in the dry season. 13 School-based randomized trials in China and Egypt found lower rates of both absenteeism and absenteeism related to certain illnesses among pupils that participated in handwashing interventions. 10,12 A handwashing trial among preschool children in Israel found no effect on overall absenteeism or absenteeism due to illness.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that schools with poor water access during the dry season that received an improved water supply also saw improvements in hygiene promotion, water treatment, and sanitation as well as increased enrolment and better gender parity within this (Garn et al, 2013). Hunter et al (2015) found a strong association between free and safe drinking water and reduced absenteeism in the dry season in Laos, suggesting that improved hydration leads to a better school experience for children. In the West Bank and the Gaza Strip a positive relationship was found between educational level and attitudes and practice of washing hands before eating (Al-Khatib et al, 2015).…”
mentioning
confidence: 89%